2023
DOI: 10.1186/s12876-023-02964-4
|View full text |Cite
|
Sign up to set email alerts
|

Non-alcoholic fatty liver disease and socioeconomic determinants in an Iranian cohort study

Zahra Sadeghianpour,
Bahman Cheraghian,
Hamid Reza Farshchi
et al.

Abstract: Background Non-alcoholic fatty liver disease (NAFLD) is widespread worldwide. On the other hand, social inequality and socioeconomic status (SES) can affect all aspects of health. Therefore, this study aimed to investigate the relationship between SES indicators and NAFLD. Methods This was a cross-sectional study using data from the registration phase of the Hoveyzeh Cohort Study, which included 10,009 individuals aged 35–70 years from May 2016 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Koutny et al [ 38 ] found a significantly higher prevalence of NAFLD based on the fatty liver index (FLI) and liver FIB-4 scores in the low education group than in the high education group. However, a recent study found that people who were categorized in the highest wealth group were significantly more likely to have high FLI scores compared to those in the low wealth category [ 39 ]. The authors speculated that this could be a result of low physical activity and high calorie intake among these individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Koutny et al [ 38 ] found a significantly higher prevalence of NAFLD based on the fatty liver index (FLI) and liver FIB-4 scores in the low education group than in the high education group. However, a recent study found that people who were categorized in the highest wealth group were significantly more likely to have high FLI scores compared to those in the low wealth category [ 39 ]. The authors speculated that this could be a result of low physical activity and high calorie intake among these individuals.…”
Section: Discussionmentioning
confidence: 99%
“…26 Recently, a significant correlation was established between skill level (skill level 1 covers the most basic positions; skill level 2 requires the effective comprehension of information like safety protocols and basic arithmetic; skill level 3 demands advanced abilities and specialised knowledge; skill level 4 entails solving intricate problems and making decisions grounded in extensive theoretical and experimental expertise within a specific area) and fatty liver index within a large middle-aged population, although no significant association was observed between sex and the presence of fatty liver. 27 Recently, an international group of experts suggested that NAFLD be redefined as metabolic dysfunction-associated steatotic liver disease (MASLD). 28 The potential effect of this change in nomenclature on the prediction of CVD risk remains uncertain.…”
Section: Non-alcoholic Fatty Liver Disease and The Prevalence Of Clin...mentioning
confidence: 99%